Ollier's disease with lower limb involvement in a Czech girl - result of complex treatment - Mařík, I; Zemková, Daniela; Myslivec, Radek; Doktorová, Helena; Povýšil, Ctibor (Pohybové ústrojí. Pokroky ve výzkumu, diagnostice a terapii, 2021)
The authors present a successful complex treatment of a Czech girl with Ollier ́s disease during the growth period, the aim of which was to correct the biomechanical axis and length of the lower limbs.
Keywords: dolní končetina; Humans; Radiography; dítě; radiografie; Child; enchondromatóza; Female; Osteogenesis, Distraction; osteogeneze pomocí distrakčního aparátu; lidé; externí fixátory; Lower Extremity Deformities, Congenital; chondrosarkom; Lower Extremity; ortopedické výkony; ženské pohlaví; vrozené deformity dolní končetiny; Orthopedic Procedures; External Fixators; Chondrosarcoma; Enchondromatosis